PAX5-Negative Classical Hodgkin Lymphoma: A Case Report of a Rare Entity and Review of the Literature - Vali Betts, Elham; Dwyre, Denis M.; Wang, Huan-You; Rashidi, Hooman H. (Case Reports in Hematology, 2017)
Classical Hodgkin lymphoma (CHL) is recognized as a B-cell neoplasm arising from germinal center or postgerminal center B-cells. The hallmark of CHL is the presence of CD30 (+) Hodgkin and Reed-Sternberg (HRS) cells with dim expression of PAX5. Nearly all of the HRS cells are positive for PAX5. However, a small minority of HRS cells may lack PAX5 expression, which can cause a diagnostic dilemma. Herein we describe two cases of PAX5-negative CHL and review of the English literature on this very rare entity. It is crucial to be aware of this phenomenon, which in some cases may lead to misdiagnosis and may ultimately adversely affect patient’s management.